Study on assessment of BMI and its correlation with various lifestyle-associated factors in mid-adolescent schoolchildren - Pandwar, Umesh; Tantuvoy, Richa; Pal, Pankaj (Indian Journal of Child Health, 2020)
Background: The problem of the double burden of malnutrition is being faced by India, in which one end consists of childhood and adolescent obesity and other end includes undernutrition. Objective: The present study aimed to assess the body mass index (BMI) and its correlation with various lifestyle-associated factors in mid-adolescent schoolchildren. Materials and Methods: The study was carried out among 605 students of classes 9th–12th of a school in Central India and in the age group of 15–17 years. The students were surveyed through an age appropriate modified Global School-Based Student Health Survey self-administered questionnaire. The height and weight were measured using standardized equipment and procedure. Results: Out of 605 schoolchildren, there were 243 (40%) males and 362 (60%) females. There was statistically significant association of BMI with hygiene habits (P = 0.001), dietary habits (P = 0.017), protective factors (P = 0.001), physical violence (P = 0.035), and dietary factor, i.e., use of vegetable in diet and use of fast food (P = 0.05). However, various other factors such as mental health, social media, and substance abuse were not found to be statistically significant. Conclusion: We found that there is a significant association present between BMI and few of the lifestyle-associated factors. Further studies of similar kind are required with the inclusion of children from different socioeconomic background particularly from affluent classes to find out more precise link between BMI and various lifestyle factors.